Introduction to Greek tragedy - Scodel, Ruth. (New York : Cambridge University Press, 2013)
"This book provides a brief and accessible introduction to Greek tragedy for students and general readers alike. Whether readers are studying Greek culture, performing a Greek tragedy, or simply interested in reading a Greek play, this book will help them to understand and enjoy this challenging and rewarding genre. An Introduction to Greek Tragedy provides background information; helps readers appreciate, enjoy, and engage with the plays themselves; and gives them an idea of the important questions in current scholarship on tragedy. Ruth Scodel seeks to dispel misleading assumptions about tragedy, stressing how open the plays are to different interpretations and reactions. In addition to general background, the book also includes chapters on specific plays, both the most familiar titles and some lesser-known plays - Persians, Helen, and Orestes - in order to convey the variety that the tragedies offer readers"--
Machine generated contents note: 1. Defining tragedy; 2. Approaches; 3. Origin, festival, and competition; 4. Historical and intellectual background; 5. Persians; 6. The Oresteia; 7. Antigone; 8. Medea; 9. Hippolytus; 10. Oedipus the King; 11. Helen; 12. Orestes; 13. Comparing the tragedians; 14. The inheritance of Greek tragedy.
Includes bibliographical references (p. 201-211) and index.
Keywords: Greek drama (Tragedy) -- History and criticism -- Handbooks, manuals, etc